Short-chain PFAS exposure during gestation and breastfeeding alters learning and memory in adulthood: possible mechanisms related to brain development - Lorenzini, Luca; Moretti, Marzia; Zanardello, Claudia; Gallocchio, Federica; Baldassarro, Vito A.; Moressa, Alessandra; Zanella, Lorenzo; Sannia, Michele; Foiani, Greta; Quadalti, Corinne; Cescatti, Maura; Burato, Valentina; et al. (Frontiers in Toxicology, 2026)
IntroductionExposure to long-chain perfluoroalkyl substances (PFASs) during development has been consistently associated with cognitive impairment and behavioural changes in humans. These concerns have led to regulatory restrictions and a shift towards short-chain PFASs as alternatives. However, experimental evidence on the neurodevelopmental impact of short-chain PFASs remains scarce, despite their increasing detection in drinking water and human biomonitoring studies.MethodsThis study provides the first experimental evidence of the neurodevelopmental toxicity of maternal exposure to the short-chain PFASs GenX and PFBA, administered before mating, throughout gestation, and during lactation.ResultsIn a rat model, offspring from exposed dams displayed significant impairments in spatial learning and cognitive flexibility in the Morris water maze. Mechanistic investigations on PFBA exposure ex vivo revealed delayed neuronal maturation, reduced expression of MAP2, PSD95 and VGLUT. Impaired neurogenesis persisted into adulthood in the hippocampus, as shown by upregulation of nestin and downregulation of doublecortin, together with dysregulated expression of neuroinflammatory genes in the hippocampus for both tested molecules.DiscussionOur findings indicate that even short-chain PFASs, currently considered safer substitutes, may disrupt brain development, leading to persistent neuroinflammation and impaired cognitive function. These results highlight an urgent need to reassess the developmental safety of short-chain PFASs and to include neurodevelopmental endpoints in future risk assessments and regulatory policies.